Bibliometric Analysis Of Flexural Pavement Road Damage On Airport-Port Main Corridor Roads Using The Pavement Condition Index (PCI) Method - Amanda, Azzhara; Rifai, Andri Irfan; Sari, Yusra Aulia; Handayani, Susanty (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Bibliometric analysis of the use of PCI methods on roads, main corridors, airports and ports is a network of research from around the world on related topics. The main objective of this study is to see trends that continue to develop in various points of view. By capturing various studies from 2000 to 2023 using Crossref sources, 1000 studies with related topics were produced. This research accompaniment uses the help of Publish or Perish, which is then processed in the VOSviewer application with the Research Information Systems (RIS) format. There is a reasonably broad relationship in research keywords produced with the dominance of rigid pavement keywords (299 studies), pavement condition index (112 studies), road damage (79 studies), rehabilitation (63 studies), and other keywords with different number variations. The results of the conclusion data regarding the development of research on pavement condition index continue to increase continuously, with the highest number in 2022 (86 studies).